Relationship between active protection in vaccinated buffaloes against haemorrhagic septicaemia and passive mouse protection test or serum antibody titres - Chandrasekaran, S.; Kennett, L.; Yeap, P.C.; Muniandy, N.; Rani, B.; Mukkur, T.K.S. (1994)
The relationship between the standard passive mouse protection test or serum antibody titres measured by indirect haemagglutination or enzyme-linked immunosorbent assays and active protection in buffaloes immunized with different types of haemorrhagic septicaemia bacterins was investigated. Groups of 2-3 buffaloes were immunized with the bacterius currently in use in Asia, viz., broth bacterin (BB), alum precipitated vaccine (APV) and oil adjuvant vaccine (OAV) either subcutaneously (BB, APV) or intramuscularly (OAV) and challenged subcutaneously with virulent organisms at different periods post-immunization. Although the passive mouse protection and indirect haemagglutination tests carried out with the pre-challenge sera from vaccinated buffaloes revealed no relationship with active protection in buffaloes, a relationship was observed between the ELISA antibody titres and protection. In contrast, a dose-response relationship was observed between the homologous active and passive mouse protection test. © 1994.